International Financial Statistics, May 2017. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper provides notes to the country tables in the monthly issues provide information about exceptions in the choice of the consumer price index and the period average exchange rate index. For a relatively small number of countries, notes in the country tables in the monthly issues indicate where alternative price indices, such as the wholesale/producer price index or a weighted average of several price indices, are used; where data constraints have made it necessary to use weighting schemes based on aggregate bilateral non-oil trade data; and where trade in services (such as tourism) has been taken into account. When a country joins the IMF, it is assigned a quota that fits into the structure of existing quotas. Quotas are considered in the light of the member's economic characteristics, and taking into account quotas of similar countries. Quotas are reviewed at intervals of not more than five years. The reviews take account of changes in the relative economic positions of members and the growth of the world economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet